2017
DOI: 10.1177/1751143717740804
|View full text |Cite
|
Sign up to set email alerts
|

Cost of treating ventilator-associated pneumonia post cardiac surgery in the National Health Service: Results from a propensity-matched cohort study

Abstract: Ventilator-associated pneumonia was associated with significant morbidity to the patients, generating significant costs. This cost was nearer to the lower end for the cost for general intensive care unit patients in privately reimbursed systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 26 publications
1
13
0
2
Order By: Relevance
“…It contributes to additional resource consumption, adding time and expense to an intensive care stay, accounting for a large proportion of all antibiotic prescriptions [ 7 ]. VAP is considered to be responsible for an additional cost of approximately $40,000 per episode in the US [ 8 , 9 ] and around £9000 in the UK [ 10 ]. The contribution of an episode of VAP to mortality is difficult to definitively ascertain because of the high number and severity of confounders amongst the at-risk population [ 4 , 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It contributes to additional resource consumption, adding time and expense to an intensive care stay, accounting for a large proportion of all antibiotic prescriptions [ 7 ]. VAP is considered to be responsible for an additional cost of approximately $40,000 per episode in the US [ 8 , 9 ] and around £9000 in the UK [ 10 ]. The contribution of an episode of VAP to mortality is difficult to definitively ascertain because of the high number and severity of confounders amongst the at-risk population [ 4 , 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Second, while VAP may not be associated with an increase in mortality, 33 it has been associated with an increase in length of ICU stay and cost of care. 34,35 Our report helps add to the understanding of risk factors for VAP, particularly non-iatrogenic risk factors. These risk factors should be taken into consideration when comparing different ICUs, even when comparing trauma ICUs in different locations.…”
Section: Discussionmentioning
confidence: 87%
“…The cost of a VAP in a UK critical care unit has been calculated in the region of £9000, while studies in the USA have calculated costs between $10 000 and $40 000. [13][14][15] Cost analyses have shown that implementing regular SSD is a cost effective strategy, in spite of the additional cost of the subglottic port endotracheal tube. [16][17][18] Meta-analysis has given a number needed to treat of 11 for SSD.…”
Section: Discussionmentioning
confidence: 99%